CAD/CAM of complex surfaces—the experience of a multi-disciplinary research team - Bauchat, J.L.; David, J.M.; Defretin, A.L.; Wattellier, A.; Caignaert, G. (Computers in industry, 1993)
For some years, our multidisciplinary research team (mathematics, computer science, mechanical design, manufacturing and dimensional control) has been working in the field of CAD/CAM of complex surfaces. The main object of the work group is the definition of criteria able to help to define the best choice of a geometrical model to describe surfaces, taking into account design, manufacturing and control constraints. The paper presents some applications, in the field of turbomachinery (blades of centrifugal or axial pumps) and in the field of biomechanics (hip prosthesis and vertebra). Problems connected with design, manufacturing and control of such surfaces are the following: (i) study of mathematical models (Bézier patches, B-splines, rational patches, etc.); (ii) choice between ruled or free form surfaces and definition of offset surfaces according to the NC machines and the tools to use; (iii) links between CAD and NC manufacturing and control. All these activities also lead to very interesting educational developments as they integrate several subjects around a common project. They are a very good approach for students as a preparation to their future industrial job.